2008
DOI: 10.1111/j.1365-2672.2008.03802.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community dynamics during the ensilage of wilted grass

Abstract: Aims:  Grass silage is the product formed by a natural lactic acid bacterial fermentation when grass is stored under anaerobic conditions, and represents an important ruminant feedstuff on farms during winter. Of the two commonly employed methods of ensiling forage, baled silage composition frequently differs from that of comparable precision‐chop silage reflecting a different ensiling environment. The aim of this study was to investigate the dynamics of the silage fermentation in wilted grass and between ensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 38 publications
5
42
0
1
Order By: Relevance
“…Members of the Proteobacteria, Xanthomonadales, Sphingomonadales, Enterobacteriales and Actinomycetales comprised the remainder of the microbiome in small grain silages. McEniry et al [65], observed that the population of Enterobacteria associated with grass silage declined within 48 h after ensiling.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the Proteobacteria, Xanthomonadales, Sphingomonadales, Enterobacteriales and Actinomycetales comprised the remainder of the microbiome in small grain silages. McEniry et al [65], observed that the population of Enterobacteria associated with grass silage declined within 48 h after ensiling.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA is separated by either gel or capillary electrophoresis according to the length of the fragments. McEniry et al (2008) investigated bacterial community dynamics in wilted grass silage using T-RFLP. The 16S rRNA genes were amplified, then digested with the restriction endonuclease MspI, and separated by electrophoresis.…”
Section: Community Analysismentioning
confidence: 99%
“…One approach for applying the power of microbial metabolism to the challenges of biofuel production involves ensiling, which is a commonly used means for enhancing the digestibility of forage and other biomass for ruminants [44,45]. The process of ensiling exploits the capacity of naturally occurring bacteria, mostly Lactobacillaceae, to ferment the sugars within lignocellulosic residues and produce a substrate that is more easily digested by ruminal microorganisms.…”
Section: Microbial Consortiamentioning
confidence: 99%